Association of Atrial Fibrillation Burden With Cardiovascular Outcomes in New‐Onset Atrial Fibrillation Complicating Myocardial Infarction - Jiachen Luo; Xiaoming Qin; Yiqian Yuan; Yiwei Zhang; Jieyun Liu; Yaoxin Wang; Guojun Zhao; Lili Xiao; Xingxu Zhang; Yuan Fang; Wentao Shi; Lei Qin; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background New‐onset atrial fibrillation (NOAF) is a common complication after acute myocardial infarction (AMI) and is associated with poor survival. Atrial fibrillation (AF) burden is used to characterize the severity of AF. However, the association of AF burden with cardiovascular outcomes in NOAF complicating AMI is poorly understood. We aimed to investigate the prognostic impact of AF burden in NOAF complicating AMI. Methods and Results This multicenter retrospective cohort study included patients with AMI without a medical history of AF who developed the first documented AF during hospitalization between January 2014 and January 2022. AF burden was defined as the percentage of time spent in AF during hospitalization. The primary outcome was a composite of cardiovascular death, heart failure hospitalization, reinfarction, or ischemic stroke. A total of 812 patients with AMI and NOAF (mean age, 72.7±10.9 years; 552 men) were included. An AF burden of 15.29% was identified as the cutoff value for prognostic stratification; 663 patients with complete follow‐up data were then classified into the low‐burden (AF burden <15.29%; n=447) and high‐burden (AF burden ≥15.29%; n=216) groups. During a median of 4.2 years of follow‐up, high AF burden was associated with an increased risk of the composite outcomes (hazard ratio [HR], 1.66 [95% CI, 1.30–2.12]; P<0.001) after multivariable adjustment. When measured as a continuous scale, increasing AF burden remained an independent predictor of the composite outcomes (HR, 1.06 per 10% AF burden [95% CI, 1.02–1.09]; P=0.004). Conclusions A greater burden of AF is associated with a higher risk of cardiovascular outcomes among patients with NOAF complicating AMI.